2020
DOI: 10.2320/matertrans.mt-m2020040
|View full text |Cite
|
Sign up to set email alerts
|

Non-Basal Dislocation Nucleation Site of Solid Solution Magnesium Alloy

Abstract: The effect of grain boundary segregation on plastic deformation was investigated using the MgY solid solution binary alloy. Deformed microstructural observations revealed many traces of prismatic ©aª dislocations as well as basal dislocations. These dislocations were nucleated at grain boundaries with segregation of yttrium element. By comparison of material factors of binary alloy, the alloying elements having low critical resolved shear stress (CRSS) of non-basal plane and large grain boundary (twin boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For instance, segregation of B at grain boundaries in Ni strengthens, H and P embrittles grain boundary cohesion [ 4 ], while S enhances grain boundary sliding at elevated temperature, and displays an excellent ductility [ 5 ]. Many alloying elements have been observed to segregate to the grain boundary in wrought processed Mg alloys [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], affecting in different ways the deformation behavior as well as other mechanical properties [ 14 , 15 ]. For example, the solute elements with an atomic radius larger than Mg are prone to embrittle the grain boundary, causing an intergranular fracture similarly to how Ca does in the Mg-Ca binary alloy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, segregation of B at grain boundaries in Ni strengthens, H and P embrittles grain boundary cohesion [ 4 ], while S enhances grain boundary sliding at elevated temperature, and displays an excellent ductility [ 5 ]. Many alloying elements have been observed to segregate to the grain boundary in wrought processed Mg alloys [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], affecting in different ways the deformation behavior as well as other mechanical properties [ 14 , 15 ]. For example, the solute elements with an atomic radius larger than Mg are prone to embrittle the grain boundary, causing an intergranular fracture similarly to how Ca does in the Mg-Ca binary alloy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bonding strength across the grain boundary is ascribed as the dominant force to resist crack propagation along the boundary. As for the influence of segregated solute elements on grain boundary sliding, several studies on metallic materials other than Mg have been reported [ 13 , 24 , 25 , 26 , 27 , 28 ]. However, to the best of our knowledge, there are not any reports on such influence in Mg and it remains largely unclear from the perspective of the electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al and Jin et al prepared a Mg alloy with 1.67 wt-% Zn, the TYS and EL of which could reach 238-256 MPa and 22-26%, respectively [10,11]. Somekawa et al reported that the microstructure of a Mg-Ca alloy underwent similar deformation to that of Mg-RE alloys [12]. The addition of Li to Mg could apparently improve the alloy plasticity, and the matrix structure was simultaneously transformed from hcp to bcc [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%